Caracterização espaço-temporal da atividade pesqueira de pargo através de dados de desembarque da região estuarina do rio Caeté , Bragança (Pará) - JIMENEZ, Érika Antunes (2019)
The large-scale landings of pargo (Lutjanidae spp.) on Caeté estuary main ports from june/00 to june/01 was characterized in this study. Data were collected with a questionnaires applied to fishermen in Bragança region. The data were treated statistically by parametric or nonparametric analysis of variance, depending of the assumptions of normality and homoscedasticity. Plots of production were constructed to distinguish the spatial and temporal catches at the Brasil north coast. 47 fishery boats were recorded operating in large-scale pargo capture, with 39 medium-sized and 8 industrial fishery boats. In the cities of Bacuriteua and Bragança there were a total of 143 landings. 65.03% occurred in Bacuriteua, possibly to be located closest to mouth of the estuary, reducing costs and time to return to the fisherie activity. 63.83% of the boats has their origin from Ceará Estate, medium-sized boats mainly, with 63% came from Camocin (CE), confirming the migration of fishery fleet to north of Brazil, searching more promising resources. During this study, a total production of 520,219t of pargo was landed, especially for medium-sized boats, responsible for 65.73% of total. The capture was made by “caicos” and “bicycles” fishery gears, the latter being responsible for 89.90% of total production. The luse of the “Caicos” was associated with low quality of the fish caught with this gears. Most of the production was captured at the coast of Amapá Estate because the fishery effort tends to concentrate in areas where the density is higher. Beside that, the North Brazil Current, carries the discharge of Amazon River to the coast of this state. The mainly catches was made at Coast of Amapá at both dry and rain seasons, with only some isolated places at Pará State coast. The CPUE index analysis showed no significant differences between months, indicating that this feature occurs throughout the year, with differential peak catches in June. A increase in production from May to August coincides with the period which the pargo schools are located near from surface. The lower production corresponded to January and April, when the schools are in areas deeper causing longer fishery traveling and thus a smaller number of landings. When the fishery boats return from fisheries, peaks of high production can be noted in February, March and May. It was estimated in this study that the pargo production was responsible for R$ 2,090,299.50, which demonstrates the high profitability of large-scale fisheries of this resource for region. Catches taken on coast of Amapá were responsible for 94.32% of total income. The average market value of the pargo at first sale was R$ 4.02, showed no major changes over the period.